Association between household second-hand smoke and low birth weight in sub-Saharan Africa - Sanni Yaya; Emmanuel Kolawole Odusina (PLoS ONE, 2025)
Background The reduction of maternal and child morbidity and mortality is essential for achieving the Sustainable Development Goals (especially goal 3 – wellbeing of mothers and children) in sub-Saharan Africa (SSA). Exposure to household second-hand smoke (SHS) has been linked to adverse birth outcomes, yet limited evidence exists on its impact on low birth weight (LBW) in SSA. This study examines the association between household SHS exposure and LBW across ten SSA countries using recent national survey data. Methods A cross-sectional study was conducted using data from the Demographic and Health Surveys (DHS) from ten SSA countries collected between 2020 and 2024. The sample included 45,684 women aged 15–49 who had given birth in the five years preceding the surveys. The primary outcome variable was LBW, defined as birth weight <2500 grams. SHS exposure was determined based on household smoking behavior. Bivariate analysis was conducted using Chi-square tests, and multivariate logistic regression models were employed to estimate adjusted odds ratios (AOR) with 95% confidence intervals (CI), controlling for maternal, household, and reproductive health factors. Results Overall, 6.3% of women reported exposure to SHS, and 11.9% of births were classified as LBW. After adjusting for potential confounders, SHS exposure was significantly associated with increased odds of LBW (AOR = 1.28; 95% CI: 1.12–1.46, p < 0.01). The association was particularly pronounced in urban areas (AOR = 1.39; 95% CI: 1.17–1.65, p < 0.01). Other significant predictors of LBW included maternal age < 20 years, lower educational attainment, low antenatal care (ANC) attendance, and socioeconomic status. Conclusion Household SHS exposure is an independent risk factor for LBW in SSA. Given the significant burden of LBW on neonatal health, policies targeting SHS reduction—such as household smoking bans and integrating SHS awareness into prenatal care—should be prioritized. Future longitudinal studies should explore causal mechanisms in greater detail.